Do cyberbullies suffer too? Cyberbullies' perceptions of the harm they cause to others and to their own mental health. (December 2013) - Campbell, Marilyn A.; Slee, Phillip T.; Spears, Barbara; Butler, Des; Kift, Sally
While it is recognized that there are serious sequelae for students who are victims of cyberbullying including depression, anxiety, lower self-esteem and social difficulties, there has been little research attention paid to the mental health of students who cyberbully. It is known that students who traditionally bully report they feel indifferent to their victims, showing a lack of empathy and that they themselves are at increased risk for psychosocial adjustment. However, there is scant research on the mental health associations for students who cyberbully or their awareness of their impact on others. The current study sought to ascertain from Australian students who reported cyberbullying others in school years 6 to 12 (10–19 years of age), their perceptions of their mental health and the harm they caused to and the impact their actions had, on their victims. Most students who cyberbullied did not think that their bullying was harsh or that they had an impact on their victims. They reported more social difficulties and higher scores on stress, depression and anxiety scales than those students who were not involved in any bullying. The implications of these findings for the mental health of the cyberbullies and for psychologists in schools who assist them, are discussed.